Violência contra a mulher em uma abordagem discursiva nas aulas de língua portuguesa em São Gabriel - RS - Martini, Vanessa Vilagrand (2019)
The construction of the dissertation was motivated by concerns about the pedagogical practice and the explored theme, with this we seek to build a proposal of pedagogical intervention from the discourse analysis about violence against women, in order to enable the student-subjects to reflect critically on the subject and lead them to assume the author position in their reading and writing gestures. As a theoretical assumption, we joined the Discourse Analysis from a materialist perspective, approaching authors such as Pêcheux (1995), Orlandi (1996), Fernandes (2017), among others. From this, we gathered a file of readings and elaborated a Discursive Didactic Unit, with reading / writing activities, which, besides promoting authorship, aimed at positioning the teacher through controversial pedagogical discourse. These activities around violence against women generated an event organized by ninth grade students, who staged skits representing situations of harassment and prejudice against women and read texts produced in class on the theme, with a view to awareness of the school community regarding the proposed theme. With this research we realize that by positioning themselves through controversial pedagogical discourse the subject-teacher creates polysemic reading conditions favorable to a discursive reading, with this the student-subjects can develop their creativity and criticality, by assuming the position of authors in their own. singular interpretation gestures, so these activities make Portuguese language teaching more meaningful.